Comparison of Postoperative Complications and Reoperation Rates of Le Fort I Osteotomies Using Demineralized Bone Matrix (DBM) or Autogenous Bone Grafts in Patients with Orofacial Clefts and Craniofacial Malformations - Noémi Sipos; Junnu Leikola; Arja Heliövaara; Eeva Kormi; Juho Suojanen (Dentistry Journal, 2025)
Background: This study aims to evaluate surgical outcomes and compares the prevalence and severity of postoperative complications and reoperations with maxillary osteotomies, focusing on the effectiveness of fixation with demineralized bone matrix (DBM) versus autogenous bone grafts (ABG) in patients with orofacial clefts and craniofacial malformations. Methods: This retrospective cohort study included 138 consecutive patients treated at the Cleft Palate and Craniofacial Center, Helsinki University Hospital, from 2014 to 2022. The cohort consisted of patients with clefts (n = 113), craniosynostosis, and craniofacial syndromes (n = 25). The DBM group (n = 103) received DBX® (Musculoskeletal Transplant Foundation, Edison, NJ, USA), while the ABG group (n = 35) received autogenous bone grafts. Surgical procedures included Le Fort I and bimaxillary osteotomies. Complications involving the maxilla or both jaws were included in the analysis. Both major and minor complications, as well as reoperations, were analyzed and compared. Results: The DBM group had 13.6% of patients with complications, while the ABG group had 20.0%. Reoperation rates were 6.8% for the DBM group and 5.7% for the ABG group. There were no statistically significant differences in complication or reoperation rates between the DBM and ABG groups. Conclusions: The findings suggest that using DBM or ABG in maxillary osteotomies does not significantly affect complication or reoperation rates, supporting DBM as a viable alternative for maxillary surgeries.